Analisis aspek keuangan pada studi kelayakan bisnis PT BCA syariah kota kediri - Binti Rahmawati, Zulfa Muasaroh (Maliki Interdisciplinary Journal, 2025)
This analysis aims to evaluate various aspects that affect the performance of BCA Syariah Kota Kediri in the context of business and operations. Some of the aspects evaluated include legal aspects, business environment, human resource management, finance, technology, and corporate social responsibility (CSR). Based on the results of the evaluation, BCA Syariah Kota Kediri showed excellent performance in most aspects, especially in terms of human resource management, technology, and compliance with environmental regulations. However, there are several areas that need to be improved, such as in marketing and marketing, where companies need to improve competitiveness through product innovation, digital marketing strategy development, and operational cost efficiency. Companies also need to focus more on social responsibility by developing more sustainable CSR programs and improving waste management and environmental management to strengthen a positive image as a company that cares about environmental sustainability. In addition, the financial and human resources aspects also need to be strengthened by further investment in technology and training for employees. Overall, BCA Syariah Kota Kediri has a strong foundation to continue to grow, but needs to make improvements and innovations in several areas in order to maintain competitiveness and achieve sustainable growth in the future